Beyond centralism - Theilmann, Axel (Technische Universität Dortmund, 2010)
Current sensor networks for Early Warning Systems (EWS) have a simple monolithic structure where data is acquired at the network edges and then transmitted over a \dumb" infrastructure to the Early Warning Center (EWC) for analysis. This structure has proven inadequate for cross-organisational EWS and inter-EWS communication. The recently started Herold research project suggests a distributed architecture for network security systems based on independent network agents. While Herold is still in an early stage and much larger in scope, its central ideas can already be applied to alleviate the problems of monolithic EWS architectures.
The Herold Approach to Sensor Networks and Early Warning Systems
Keywords: 004